The influence of tall buildings on the pedestrian level micro-climate in Lujiazui New District, Shanghai - Yao, Jiawei (2016)
In relation to Chinese cities, both thermal comfort and urban air ventilation have been researched extensively in the past decades while the quality of open urban spaces have received increasing attention in developed countries in recent years. However, there has been relatively little research addressing how microclimatic conditions also contribute to the quality of life. This thesis aims to obtain the local outdoor thermal comfort criteria, assess the wind environment around the built tall buildings and suggest an approach for urban design. To achieve that, winter outdoor thermal comfort will be determined through a pedestrian thermal comfort questionnaire survey and monitoring of site climatic conditions help to generate local thermal comfort criteria. Summer comfort conditions were determined from an analysis of the literature. After that, the wind environment will be simulated with wind tunnel tests and computational numerical modelling. This will be assessed to improve outdoor wind comfort in urban areas and to build more comfortable and healthier open spaces for pedestrians. Nevertheless, after the creation of the Lujiazui Financial Centre in the Pudong district of Shanghai, a high-density area, with a huge number of tall buildings and the core of the economic development, further improvement has been planned. According to the questionnaire on thermal comfort and the meteorological data retrieved from the monitoring of the site, the majority of participants were satisfied with the outdoor thermal environment found in Lujiazui during the winter and a series of findings demonstrated that microclimate is a very important parameter for outdoor thermal comfort. For instance, it was observed that: (a) the mean neutral air temperature is 14.7℃ and the accepted temperature range is 7.7℃ to 21.8℃; (b) the neutral global radiation is 856W/m2; (c) the neutral air humidity is 67%; and (d) the neutral wind velocity is 0.55m/s with an accepted wind velocity range of 0-3.2m/s in winter. Furthermore, the application of wind tunnel tests and computational numerical modelling simulations revealed that the microclimate of an environment would be affected every time a new building is erected. This is why, especially in rapidly developing areas characterised by high-density, generating high-speed winds at the pedestrian level in order to increase air circulation and therefore create a healthier environment in terms of air quality is not uncommon, although these man-made air flows may be perceived as distressful or unsafe. In the light of such conditions, when designing a new building its morphology, its influence on the interior environment, and its impact on the outdoor environment should be equally taken into account. Furthermore, some suggestions for optimised urban design methods about building more skyscrapers in the extended area of Lujiazui are provided, which could become a guideline for the government and the urban designers with the aim to create better, more comfortable and healthier urban open spaces in a sustainable city.